First report of two eulophid genera (Hymenoptera: Chalcidoidea: Eulophidae) from India with the description of two new species - Ranjith, A.p.; Burks, Roger A.; Femi, E.b.; Priyadarsanan, Dharma Rajan (Zootaxa, 2023)
The eulophid genera Dermatopelte Erdös & Novicky and Iniostichus Kamijo & Ikeda are reported for the first time from India. Two new species, Dermatopelte striata n. sp. and Iniostichus proximus n. sp. are described and illustrated. A revised key to the Indo-Malayan species of Dermatopelte and a key to the extant species of Iniostichus are included.